Identification of atypical mitogen-activated protein kinase MAPK4 as a novel regulator in acute lung injury - Ling Mao; Ya Zhou; Longqing Chen; Lin Hu; Shiming Liu; Wen Zheng; Juanjuan Zhao; Mengmeng Guo; Chao Chen; Zhixu He; Lin Xu (Cell & Bioscience, 2020)
Abstract Background Acute lung injury (ALI) is a serious disease with highly morbidity and mortality that causes serious health problems worldwide. Atypical mitogen activated protein kinases (MAPKs) play critical roles in the development of tissues and have been proposed as promising therapeutic targets for various diseases. However, the potential role of atypical MAPKs in ALI remains elusive. In this study, we investigated the role of atypical MAPKs family member MAPK4 in ALI using LPS-induced murine ALI model. Results We found that MAPK4 deficiency mice exhibited prolonged survival time after LPS challenge, accompanied by alleviated pathology in lung tissues, decreased levels of pro-inflammatory cytokines and altered composition of immune cells in BALF. Furthermore, the transduction of related signaling pathways, including MK5, AKT, JNK, and p38 MAPK pathways, was reduced obviously in LPS-treated MAPK4−/− mice. Notably, the expression of MAPK4 was up-regulated in lung tissues of ALI model, which was not related with MAPK4 promoter methylation, but negatively orchestrated by transcriptional factors NFKB1 and NR3C1. Further studies have shown that the expression of MAPK4 was also increased in LPS-treated macrophages. Meanwhile, MAPK4 deficiency reduced the expression of related pro-inflammatory cytokines in macrophage in response to LPS treatment. Finally, MAPK4 knockdown using shRNA pre-treatment could ameliorate the pathology of lung tissues and prolong the survival time of mice after LPS challenge. Conclusions Collectively, these findings reveal an important biological function of atypical MAPK in mediating the pathology of ALI, indicating that MAPK4 might be a novel potential therapeutic target for ALI treatment.